In vitro Evaluation of Sesquiterpenoid Extracts of Phellinus Samples from Western Ghats of Maharashtra for Antimicrobial Activity - Sandhya Garad1, Gauri Bapat1, Mugdha Belsare1, Hiralal Sonawane1*, Shekhar Bhosle2, Jitendra Vaidya1, Asghar sharifi1 (Journal of Phytology, 2011)
Phellinus Quel. is a folk medicinal, wood inhabiting fungus special, recently been studied for its pharmacological activities. In the current study, sesquiterpenes extracted from six species of Phellinus viz. P. fastuosus, P. merrillii, P. aureobruneus, P. crocatus, P. lloydii and P. sublinteus were tested aginst twelve virulent strains of bacteria and fungi. A significant broad spectrum anti-bacterial and aniti-fungal activity of sesquiterpenes isolated from Phellinus spp. was revealed through the study.